How online sexual health services could work; generating theory to support development. Issue 1 (June 2015) - Baraitser, Paula; Syred, Jonathan; Spencer-Hughes, Vicki; Howroyd, Chris; Free, Caroline; Holdsworth, Gillian
Abstract Background Online sexual health services are an emerging area of service delivery. Theory of change critically analyses programmes by specifying planned inputs and articulating the causal pathways that link these to anticipated outcomes. It acknowledges the changing and contested nature of these relationships. Methods We developed two versions of a theory of change for an online sexual health service. The first articulated the theory presented in the original programme proposal and the second documented its development in the early stages of implementation through interviews with key programme stakeholders. Results The programme proposal described an autonomous and empowered user completing a sexual health check using a more convenient, accessible and discreet online service and a shift from clinic based to online care. The stakeholder interviews confirmed this and described new and more complex patterns of service use as the online service creates opportunities for providers to contact users outside of the traditional clinic visit and users move between online and clinic based care. They described new types of user/provider relationships which we categorised as: those influenced by an online retail culture; those influenced by health promotion outreach and surveillance and those acknowledging the need for supported access. Conclusions This analysis of stakeholder views on the likely the impacts of online sexual health services suggests three areas for further thinking and research.1. Co-development of clinic and online services to support complex patterns of service use. 2. Developing access to online services for those who could use them with support. 3. Understanding user experience of sexual health services as increasing user autonomy and choice in some situations; creating exclusion and a need for support in others and intrusiveness and a lack of control in still others. This work has influenced the evaluation of this programme which will focus on; mapping patterns of use to understand how users move between the online and clinic based services; barriers to use of online services among some populations and how to overcome these; understanding user perceptions of autonomy in relation to online services.